SCAN-NF : a machine learning system for invoice product trasaction classification through short-text processing - Kieckbusch, Diego Santos (2022)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2022.